Keynes's approach to full employment: aggregate or targeted demand? - Pavlina R. Tcherneva (Levy Economics Institute of Bard College, 2008)
This paper argues that John Maynard Keynes had a targeted (as contrasted with aggregate) demand approach to full employment. Modern policies, which aim to close the demand gap, are inconsistent with the Keynesian approach on both theoretical and methodological grounds. Aggregate demand tends to increase inflation and erode income distribution near full employment, which is why true full employment is not possible via traditional pro-growth, pro-investment aggregate demand stimuli. This was well understood by Keynes, who preferred targeted job creation during expansions. But even in recessions, he did not campaign for wide-ranging aggregate demand stimuli; this is because different policies have different employment creation effects, which for Keynes was the primary measure of their effectiveness. There is considerable evidence to argue that Keynes had an on the spot approach to full employment, where the problem of unemployment is solved via direct job creation, irrespective of the phase of the business cycle.
Keywords: E01; E12; E62; B31; 330; John Maynard Keynes; public works; fiscal policy; full employment; aggregate demand; targeted demand; demand gap analysis